Tradition ingush cradle and associated and customs - Ruket H. Doskhoeva (Кавказология, 2025)
This article examines the rite of placing a baby in a traditional Ingush cradle, the aga, as well as the customs and beliefs of the people associated with it. The source was field ethnographic material collected in July 2023-2024 in the settlements of the Republic of Ingushetia and in the Prigorodny district of the Republic of North Ossetia–Alania. In this article, the author emphasizes that rituals associated with important events in human life are one of the key characteristics of the traditional culture of the people. In particular, rituals related to the birth and upbringing of children play an important role in shaping a culture of behavior and transferring values from one generation to another. The author notes that these rituals have socio-historical, cultural, ideological, and educational significance. In addition, they reflect the uniqueness of the mentality and worldview of the people. In conclusion, the author concludes that the functions of the aga cradle have undergone a certain transformation under the influence of globalization, socio-cultural and modern processes that have occurred in society under the influence of the re-Islamization of recent decades.